(untitled) (Global Journal of Management and Business Research, 2023)
With advancements in technology now diffuse in all dimensions of business and social life artificial intelligence AI has found its place in human resource management HRM assisting in the recommendation and selection of suitable candidates for specific jobs In this regard AI is used to improve the productivity of HR personnel and mitigate bias in candidate selection This research discusses the background and applications of AI in HRM its current benefits and limitations and suggests potential future pathways in this domain